Evaluation of cutaneous microcirculation in systemic sclerosis. An update - Katarzyna Pawlik; Anna Bohdziewicz; Magdalena Maciejewska; Jefte Prado; Joanna Czuwara; Małgorzata Olszewska; Lidia Rudnicka (Termedia Publishing House, 2023)
The impairment of the microcirculation is a crucial aspect of systemic sclerosis which manifests as a plethora of vascular abnormalities. This review examines the methods used in the evaluation of the changes to the microcirculation. Nailfold capillaroscopy is the most routinely used technique in the assessment of the microcirculation added to the SSc classification criteria of the American College of Rheumatology (ACR) and European League Against Rheumatism (EULAR). The "fast track algorithm" allows a scleroderma pattern to be distinguished from a non-scleroderma pattern. The algorithm consists of three rules focusing on capillary density and the absence or presence of giant capillaries. Other techniques include laser doppler flowmetry, laser speckle contrast analysis, laser doppler imaging, optical coherence tomography angiography, fluorescence optical imaging, optical near-infrared spectroscopy, 99mTc-pertechnetate hand perfusion scintigraphy, and thermography. Knowledge of the methods of assessing microcirculation disorders in patients with systemic sclerosis allows for their optimal use.